A change of space: implications of digital fieldwork in connected homes during the COVID-19 pandemic. Issue 3 (3rd July 2022) - Paupini, Cristina; Teigen, Helene Fiane; Habib, Laurence
ABSTRACT: Drawing on research conducted in ten Norwegian households, this article describes the effects that the COVID-19 pandemic and social distancing regulations have had on the research design and, consequently, on research data. The article describes how the research design had to be adapted to a variety of containment measures that were imposed during the fieldwork, and how this has influenced the researchers' rapport with informants and access to the field and the challenges that emerged. It also describes a more active role for the participants in the study, whose agency was enhanced. The article proposes a new way of approaching fieldwork in homes adopting 'methodological improvisation' and concludes with recommendations for future research, proposing digital ethnography methods as both an option that enables data collection during a pandemic and as a sustainable alternative to certain methodologies that belong to traditional ethnography.